Rubber Transferase Activity and Rubber Particle Sizes Derived from Lactarius Mushrooms - Ieda, Takeshi; Nakamura, Takeshi; Inoue, Yukino-Miyagi; Ohya, Norimasa (Asian Journal of Chemistry, 2013)
Upon cutting the fruiting body of L. volemus, a white latex was exuded that changed gradually to a brown colour. The rubber particles from L. volemus showed a bimodal or trimodal particle size distribution with a mean diameter of 1.10-1.32 μm. A comparison with Hevea showed that the rubber particles size in L. volemus latex was slightly larger than those of Hevea, but showed a similar distribution curve. Five Lactarius mushrooms were also examined and showed the characteristic particle size distributions, which varied according to species, suggesting a certain mechanism for controlling the particle size. The in vitro rubber biosynthesis using the rubber particles of L. volemus is also reported.